2010
DOI: 10.1107/s0021889809054983
|View full text |Cite
|
Sign up to set email alerts
|

Local atomic structure in tetragonal pure ZrO2nanopowders

Abstract: The local atomic structures around the Zr atom of pure (undoped) ZrO2 nanopowders with different average crystallite sizes, ranging from 7 to 40 nm, have been investigated. The nanopowders were synthesized by different wet‐chemical routes, but all exhibit the high‐temperature tetragonal phase stabilized at room temperature, as established by synchrotron radiation X‐ray diffraction. The extended X‐ray absorption fine structure (EXAFS) technique was applied to analyze the local structure around the Zr atoms. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
15
0
6
Order By: Relevance
“…Several XAS studies have been reported to date for solid ZrO 2 -Y 2 O 3 solutions or nanocrystalline YSZ materials for which the structural disorder plays an important role. 27,28 The results were controversial, mainly due to the interpretation of the coordination numbers and Debye-Waller factors extracted from EXAFS. 29 For this reason not only the EXAFS spectra but also the XANES region, more sensitive to the bonding geometry and stereochemical details, have been analyzed in order to reduce the possible arbitrariness of the EXAFS results arising from the large uncertainties in coordination numbers and Debye-Waller factors due to their strong correlation.…”
Section: Resultsmentioning
confidence: 99%
“…Several XAS studies have been reported to date for solid ZrO 2 -Y 2 O 3 solutions or nanocrystalline YSZ materials for which the structural disorder plays an important role. 27,28 The results were controversial, mainly due to the interpretation of the coordination numbers and Debye-Waller factors extracted from EXAFS. 29 For this reason not only the EXAFS spectra but also the XANES region, more sensitive to the bonding geometry and stereochemical details, have been analyzed in order to reduce the possible arbitrariness of the EXAFS results arising from the large uncertainties in coordination numbers and Debye-Waller factors due to their strong correlation.…”
Section: Resultsmentioning
confidence: 99%
“…The first peak corresponds to the contribution of the first oxygen shell around the Zr absorber, while the second peak contains information related to Zr Zr coordination. At the same temperature, different parameters can influence the intensity of these peaks such as: the degree of reduction, the crystallite size [59], and the local order in the system [60].…”
Section: Exafs and Xanes Under H 2 Reduction Conditionsmentioning
confidence: 99%
“…Contudo, apesar de muitos estudos experimentais, pouco tem sido estudado do ponto de vista teórico sobre propriedades estruturais e impurezas em zircônia. Materiais baseados em zircônia têm sido muito investigados devidoàs suas grandes aplicações tecnológicas como calalizadores [1], células solares e sensores de oxigênio [2,3]. A zircônia apresenta 3 fases estruturais, dependendo da temperatura.…”
Section: Capítulo 1 Introduçãounclassified
“…A zircônia apresenta 3 fases estruturais, dependendo da temperatura. Até 1170 • C sua fase mais estávelé a monoclínica, de 1170 • C até 2370 • C a fase tetragonalé a mais estável e acima de 2370 • C até seu ponto de fusão (2780 • C) a estruturaé cúbica [2]. As fases mais importantes para aplicações práticas são a tetragonal e a cúbica.…”
Section: Capítulo 1 Introduçãounclassified
See 1 more Smart Citation